Pengaruh Live Streaming Dan E-Trust Terhadap Impulsive Buying Produk Oclo.Official Pada Platform Shopee Di Kalangan Mahasiswa Universitas Pamulang - Andy Nuryanto; Hadi Susanto; Sherina Aprilia Zanetra; Ria Aulia (CV. ITTC INDONESIA, 2026)
This study aims to analyze the influence of Live Streaming and E-Trust on Impulsive Buying of Oclo.Official products on the Shopee platform among students of Universitas Pamulang. The study employed a quantitative method with a descriptive associative approach. The population consisted of Universitas Pamulang students who had watched Shopee Live and were familiar with Oclo.Official products, using purposive sampling technique. Data were collected through questionnaires and analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and coefficient of determination. The results show that Live Streaming partially has a positive and significant effect on Impulsive Buying (t-value = 5.386; sig. = 0.000). E-Trust also has a positive and significant effect on Impulsive Buying (t-value = 5.768; sig. = 0.000). Simultaneously, Live Streaming and E-Trust have a positive and significant effect on Impulsive Buying (F-value = 72.164; sig. = 0.000), contributing 60.6% of the variance. The better the quality of Live Streaming and the higher the level of E-Trust, the greater the tendency of consumers to engage in Impulsive Buying.